2021
DOI: 10.1021/acs.jafc.1c00721
|View full text |Cite
|
Sign up to set email alerts
|

Propeptide in Rhizopus chinensis Lipase: New Insights into Its Mechanism of Activity and Substrate Selectivity by Computational Design

Abstract: Most fungal lipases contain a propeptide, which is very important for their function and substrate selectivity. In the present study, Rhizopus chinensis lipase (RCL) was used as a research model to explore the mechanism of the propeptide of the lipase. Conventional molecular dynamics (MD) and metadynamics simulations were used to explore the mechanism by which the propeptide affects the activity of the lipase, which was subsequently verified by mutation experiments. MD simulations indicated that the propeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…The DCC algorithm is unchanged from that of MD-TASK, with the exception that it is now faster and supports additional atom types. Some of the recent examples from the published literature that used the MD-TASK DCC functionality include [16] , [17] , [18] , [21] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DCC algorithm is unchanged from that of MD-TASK, with the exception that it is now faster and supports additional atom types. Some of the recent examples from the published literature that used the MD-TASK DCC functionality include [16] , [17] , [18] , [21] .…”
Section: Resultsmentioning
confidence: 99%
“…Both MD-TASK and MODE-TASK have been highly utilized to mine protein dynamics by offering a series of novel approaches that have demonstrated their applicability in a growing number of cases [6] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] . Although both software suites are relatively easy to use, the required technical knowledge and software dependencies may act as a hurdle against more widespread usage of the tools and techniques, due to the diversity of operating systems and the relatively fast-evolving Python libraries.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Lip2 and BCL exhibited a more complex lid motion, which was described as a "double-domain" motion (Barbe et al, 2009;Cheng, Angkawidjaja, Koga, & Kanaya, 2012;Jiang et al, 2014). In contrast, another recent study has revealed an inhibitory effect of the peptide fragment on lid motion (Wang, Xu, et al, 2021). The above complex structural transitions highlighted the importance of other domains in lid dynamics and lipase catalysis.…”
Section: Typical Lid Motionmentioning
confidence: 96%
“…Recently, MD simulation has provided an atomic-level description of lid motion on temporal and energetic scales, thereby predicating the correlation between the lid dynamics/conformation and the function of the lipase. Moreover, molecular simulations allow us to confirm the inhibitory or promoting effects of other regions on the lid motion (Riccardi et al, 2017;Wang, Xu, et al, 2021). By integrating extensive computational simulations and free-energy calculations with mutagenesis and kinetic experiments, a lid-domain-mediated mechanism for substrate selection and binding in lipase catalysis has been elucidated (Xu et al, 2010).…”
Section: Computational Design To Rebuild the Lidmentioning
confidence: 99%
“…For the RCL systems, the major differences of RMSF existed in the N-terminal propeptide region. Following a previous study, the N-terminal propeptide of RCL plays an important role in its function [39]. Moreover, the lid region of RCL in the The quantitative root-mean-square fluctuation (RMSF) was evaluated for the backbone atoms of lipases for all systems (Figure 2).…”
Section: Overall Conformations Of Lipases In Different Solvent Environmentsmentioning
confidence: 99%